If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9h + -2h = -16 Combine like terms: 9h + -2h = 7h 7h = -16 Solving 7h = -16 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Divide each side by '7'. h = -2.285714286 Simplifying h = -2.285714286
| m/4+7=-2 | | 5(3p-10)-5q=-15 | | y=1.75x-15 | | 1/4*12-(3*y)+3/4y=3 | | 5x-4x-6=3-2x | | 12z-28z+5z=-6z+7-22 | | 4+7w=32 | | 2/3+1/2= | | 2x+18=18x | | 5/6=2x | | 8x=3+5x | | 3(y+2)=32y | | y=5+-3 | | sqr(-16)= | | (2y)+4x=8 | | -30x=6 | | w-9/w-9w-53/11w | | 7(-5x-5)=245 | | 7x+12=4x-5 | | x^5+2x^3-297=0 | | 5x+4x-60=30-6x | | x^4-26x^2=25 | | (1/2x)+15=8x | | 4*x=11 | | 893x-20=80 | | x=4*(3-(3/4*y)) | | (3x+8)+(5x+4y)+(5x-20)=180 | | 5x^2+xy+6y^2=80 | | 24-2h=12 | | 2(7+5)-3y=-35 | | 24=9x+4-5x | | 5+x/2=12 |